2006
DOI: 10.1111/j.1440-1843.2006.00835.x
|View full text |Cite
|
Sign up to set email alerts
|

Gefitinib‐induced interstitial lung disease showing improvement after cessation: Disassociation of serum markers

Abstract: Gefitinib (ZD1839), a small-molecule epidermal growth factor receptor tyrosine kinase inhibitor, is an anticancer agent for patients with non-small cell lung carcinoma. Recently, however, as a result of accumulating evidence, it has been recognized that gefitinib can give rise to lethal lung toxicity. The authors report a case of interstitial lung disease (ILD) induced by gefitinib, which improved promptly following cessation of the administration of the agent. Clinical signs suggesting a good prognosis were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…Although GEF was considered well tolerated, various adverse effects associated with GEF have been reported in clinical practice, such as diarrhea (49%), rash (44%) [3,4], life-threatening interstitial lung disease (ILD) and liver injury. The over incidences of GEF-induced ILD is about 1%, but approximately 1/3 of the cases can be fatal [5][6][7]. Liver injury associated with GEF accounted for 2% to 4% of patients, which can lead to discontinuations of therapy and even death [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Although GEF was considered well tolerated, various adverse effects associated with GEF have been reported in clinical practice, such as diarrhea (49%), rash (44%) [3,4], life-threatening interstitial lung disease (ILD) and liver injury. The over incidences of GEF-induced ILD is about 1%, but approximately 1/3 of the cases can be fatal [5][6][7]. Liver injury associated with GEF accounted for 2% to 4% of patients, which can lead to discontinuations of therapy and even death [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Corticosteroid therapy for both episodes effectively relieved the symptoms and made improvement in radiologic findings. It shows a clinical similarity to recurrent gefitinib-induced ILD 10,11 which is reported that pathogenesis of EGFR-induced ILD is immunological activation rather than direct drug cytotoxicity because of good response for corticosteroid, shortening of second attack period and more severe ILD recurrence than the first occurrence. Even though our case showed acute interstitial pneumonia (AIP) pattern with extensive bilateral ground-glass appearance on chest CT that was thought as a poor prognosis group 3 , obviously our patient was a good responder to erlotinib based on Chest CT finding that showed dramatic decrease of metastatic lung lesions.…”
Section: Discussionmentioning
confidence: 74%
“…Cough and dyspnea are presented as initial symptom of ILD at 6 days to 9 months after initiation of treatment and it shows more variable onset time than geftinib 1 ; gefitinib-induced ILD occurred with median time to symptom development being 24 to 31 days in Japan and 42 days in United States 8,10,11 . Diagnosis of erlotinib-induced ILD is mainly dependent on symptoms following erlotinib medication and radiologic finding that is shown as a newly developed ground grass opacitiy 2,9 .…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, discontinuation of gefitinib alone, with no further treatment has been reported to be sufficient to obtain an improvement, [3] whereas in other cases, treatment with high-dose corticosteroids appears to be needed [4]. In all of these reports of successful outcomes, the diagnosis of gefitinib-induced ILD was made before the respiratory failure had become severe.…”
Section: Discussionmentioning
confidence: 94%